CD8+ T cells produce a dialyzable antigen-specific activator of dendritic cells. Issue 1 (11th August 2016) - Myles, Ian A; Zhao, Ming; Nardone, Glenn; Olano, Lisa R; Reckhow, Jensen D; Saleem, Danial; Break, Timothy J; Lionakis, Michail S; Myers, Timothy G; Gardina, Paul J; Kirkpatrick, Charles H; Holland, Steven M; et al.
Abstract : Lysates from CD8 + T cells transfer passive IL-17-mediated cellular immunity through elements of the TCR and S100; an opportunity to elucidate the structure, role, and therapeutic potential. Abstract: Cellular lysates from PPD + donors have been reported to transfer tuberculin reactivity to naïve recipients, but not diphtheria reactivity, and vice versa. A historically controversial topic, the terms "transfer factor" and "DLE" were used to characterize the reactivity-transferring properties of lysates. Intrigued by these reported phenomena, we found that the cellular extract derived from antigen-specific memory CD8 + T cells induces IL-6 from antigen-matched APCs. This ultimately elicits IL-17 from bystander memory CD8 + T cells. We have identified that dialyzable peptide sequences, S100a9, and the TCR β chain from CD8 + T cells contribute to the molecular nature of this activity. We further show that extracts from antigen-targeted T cells enhance immunity to Staphylococcus aureus and Candida albicans . These effects are sensitive to immunization protocols and extraction methodology in ways that may explain past discrepancies in the reproducibility of passive cellular immunity.